Water and wastewater technology - Hammer, Mark J. , 1957-; Hammer, Mark J. , 1957- (Upper Saddle River, New Jersey : Prentice Hall, 2012)
Overview: The new edition of Water and Wastewater continues its traditional coverage of water processing principles and modern management practices, but now integrates a new emphasis on sustainability throughout. Comprehensive coverage of such topics as: Water processing; Water distribution; Wastewater collection; Conventional and advanced wastewater treatment; Sludge processing. Key and New Features include: Coverage of new technologies; Water supply and water sustainability woven throughout; Coverage of energy reduction opportunities, and other processes important to water sustainability; Extensive use of illustrations to explain concepts and demonstrate modern equipment and facilities; Extensive use of charts, diagrams, and tables to make the mathematics more accessible
1. Introduction -- 2. Chemistry -- 3. Biology -- 4. Hydraulics and hydrology -- 5. Water quality -- 6. Water distribution systems -- 7. Water processing -- 8. Operation of waterworks -- 9. Wastewater flows and characteristics -- 10. Wastewater collection systems -- 11. Wastewater processing -- 12. Wastewater systems capacity and asset management -- 13. Advanced wastewater treatment -- 14. Water reuse -- 15. Sustainability and carbon footprint
Includes index
Keywords: Sewage disposal; Water-supply engineering